Virtual roaming systems for GSM, GPRS, and UMTS : open connectivity in practice - e uthor.9; IEEE Xplore (Online Service); Wiley (Chichester, West Sussex, U.K. ; John Wiley, 2009)
This book provides a detailed technical guide to the virtual and optimised roaming systems for mobile networks Written by a pioneer in the field, this book focuses on the implementation of virtual roaming systems. It generalizes the previous SS7 SMS interworking architectures to voice and data, GPRS, and 3G virtual roaming; extending the discussion of virtual roaming to include location based services, optimal routing and 4G perspectives. The author provides a thorough and detailed technical explanation of the topic covering subjects such as 'Over the Air' (OTA) provisioning and detailed geo-localisation systems in a virtual roaming environment. Finally, this book addresses the application of MAP, CAMEL, TCAP, SCCP, and GTP. Key Features: *Provides a thorough and detailed technical coverage of virtual and optimised roaming systems for mobile networks *Explores the application of MAP, CAMEL, TCAP, SCCP, and GTP *Discusses previous SMS Hubs architecture used for SMS interworking and generalises to voice, data, and 3G virtual roaming *Includes material on pre-paid case with CAMEL parameter transformations, SMS, Supplementary Services and USSD implementation *Focuses on roaming hubs (including an, introduction to Sigtran configuration) and transparent networks of hubs This book will serve as an invaluable reference for network and networking engineers, handset developers, systems implementers, systems integrators, systems software engineers and programmers, wireless specialists and anybody else seeking a comprehensive and practical guide to the basics of virtual roaming systems.
9.1 The Data Access Path in GSM: Purpose of GPRS Profile Settings 167 -- 9.2 Obtaining the IMEI of a Handset for Device Management 168 -- 9.3 Method to Remotely Check that a Loaded GPRS Profile Works 172 -- 9.4 Architecture of a Classical OTA GPRS Server 173 -- 9.5 Stochastic Automatic GPRS Profile Type Learning OTA Server 174 -- 9.6 Stochastic Convergence 176 -- 9.7 Best Order to Try an Unknown Handset GPRS Profile Type 177 -- References and Further Reading 178 -- 10 Current Developments and Directions: GSM-UMTS ↔?nVoIP Roaming 179 -- 10.1 Pirate Techniques? 179 -- 10.2 Seamless 'Free Roaming'? GSM-UMTS with SS7 ↔?nVoIP Gateways 180 -- 10.3 Attracting the Visitors and Forcing Them to Roam Immediately in a Given VPLMN 184 -- 10.4 IMS, the all IP Network Architecture 186 -- 10.5 Making a 4G 'IP Call' to a Mobile 187 -- References and Further Reading 189 -- 11 Worked-out Examples 191 -- 11.1 Examples of Chapter 1 191 -- 11.2 Examples of Chapter 3: Roaming Hub with Several Point Codes 215 -- 11.3 Examples of Chapter 4 221 -- Index 303.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 10/24/2017.
Keywords: Roaming (Telecommunication); Electronic books